Metformin Improves Insulin Signaling in Obese Rats via Reduced IKKβ Action in a Fiber-Type Specific Manner - Benjamin T. Bikman; Donghai Zheng; Daniel A. Kane; Ethan J. Anderson; Tracey L. Woodlief; Jesse W. Price; G. Lynis Dohm; P. Darrell Neufer; Ronald N. Cortright (Hindawi Limited, 2010)
Metformin is a widely used insulin-sensitizing drug, though its mechanisms are not fully understood. Metformin has been shown to activate AMPK in skeletal muscle; however, its effects on the inhibitor of κB kinaseβ (IKKβ) in this same tissue are unknown. The aim of this study was to (1) determine the ability of metformin to attenuate IKKβ action, (2) determine whether changes in AMPK activity are associated with changes in IKKβ action in skeletal muscle, and (3) examine whether changes in AMPK and IKKβ function are consistent with improved insulin signaling. Lean and obese male Zuckers received either vehicle or metformin by oral gavage daily for four weeks (four groups of eight). Proteins were measured in white gastrocnemius (WG), red gastrocnemius (RG), and soleus. AMPK phosphorylation increased (P<.05) in WG in both lean (57%) and obese (106%), and this was supported by an increase in phospho-ACC in WG. Further, metformin increased IκBα levels in both WG (150%) and RG (67%) of obese rats, indicative of reduced IKKβ activity (P<.05), and was associated with reduced IRS1-pSer307 (30%) in the WG of obese rats (P<.02). From these data we conclude that metformin treatment appears to exert an inhibitory influence on skeletal muscle IKKβ activity, as evidenced by elevated IκBα levels and reduced IRS1-Ser307 phosphorylation in a fiber-type specific manner.